Sustainability in logistic hubs: a decision support system for investigating green practices at container terminals. (16th July 2019) - Longo, Francesco
Logistic hubs, and especially container terminals, are today responsible for a major percentage of the environmental pollution. Practices such as the onshore power supply (OPS) may have relevant benefits but it has been argued that container terminal operators perceive a paucity of evidence that the benefits derived from the implementation of these practices exceed the investment costs. To this end, an advanced simulation-based decision support system is proposed in this article to represent a reliable test environment to simulate and compare different alternatives in terms of environmental impacts and economic sustainability. The implementation of an OPS system is considered as case study. Results show that an OPS system must consider the source of the electric power needed by ships at berth, i.e., coal, biofuels or renewable energies. The unit costs of 1 m 3 of saved CO2 and NOX by implementing an OPS system are also calculated.